Mitochondrially mediated synergistic cell killing by bile acids - Rolo, Anabela P. (2003)
The accumulation of endogenous bile acids contributes to hepatocellular damage during cholestatic liver disease. To examine the controversy regarding the therapeutic use of ursodeoxycholate (UDCA) in cholestatic patients, we investigated the possible cytoprotection or synergistic effects of UDCA against chenodeoxycholate (CDCA)-induced injury to isolated rat hepatocytes. Our aim was to investigate the role of the mitochondrial permeability transition (MPT) in the mechanism of cytotoxicity caused by UDCA plus CDCA. Although not toxic by itself, UDCA potentiated the mitochondrial depolarization, ATP depletion and cell killing caused by CDCA. Fructose maintained ATP levels and prevented bile acid-induced cell killing. Cyclosporine A (CyA), a potent inhibitor of the MPT, substantially reduced mitochondrial depolarization, ATP depletion and cell killing caused by CDCA. Our results demonstrate that the synergistic cytotoxicity by UDCA plus CDCA is mediated by impairment of mitochondrial function, an event that is expressed via induction of the MPT.